Quantitative Contributions of Target Alteration and Decreased Drug Accumulation to Pseudomonas aeruginosa Fluoroquinolone Resistance - Bruchmann, Sebastian (American Society for Microbiology, 2013)
Quinolone antibiotics constitute a clinically successful and widely used class of broad-spectrum antibiotics; however, the emergence and spread of resistance increasingly limits the use of fluoroquinolones in the treatment and management of microbial disease. In this study, we evaluated the quantitative contributions of quinolone target alteration and efflux pump expression to fluoroquinolone resistance in Pseudomonas aeruginosa. We generated isogenic mutations in hot spots of the quinolone resistance-determining regions (QRDRs) of gyrA, gyrB, and parC and inactivated the efflux regulator genes so as to overexpress the corresponding multidrug resistance (MDR) efflux pumps. We then introduced the respective mutations into the reference strain PA14 singly and in various combinations. Whereas the combined inactivation of two efflux regulator-encoding genes did not lead to resistance levels higher than those obtained by inactivation of only one efflux regulator-encoding gene, the combination of mutations leading to increased efflux and target alteration clearly exhibited an additive effect. This combination of target alteration and overexpression of efflux pumps was commonly observed in clinical P. aeruginosa isolates; however, these two mechanisms were frequently found not to be sufficient to explain the level of fluoroquinolone resistance. Our results suggest that there are additional mechanisms, independent of the expression of the MexAB-OprM, MexCD-OprJ, MexEF-OprN, and/or MexXY-OprM efflux pump, that increase ciprofloxacin resistance in isolates with mutations in the QRDRs.